Toward a large‐scale and deep phenological stage annotation of herbarium specimens: Case studies from temperate, tropical, and equatorial floras. (20th March 2019) - Lorieul, Titouan; Pearson, Katelin D.; Ellwood, Elizabeth R.; Goëau, Hervé; Molino, Jean‐Francois; Sweeney, Patrick W.; Yost, Jennifer M.; Sachs, Joel; Mata‐Montero, Erick; Nelson, Gil; Soltis, Pamela S.; Bonnet, Pierre; et al.
Abstract : Premise of the Study: Phenological annotation models computed on large‐scale herbarium data sets were developed and tested in this study. Methods: Herbarium specimens represent a significant resource with which to study plant phenology. Nevertheless, phenological annotation of herbarium specimens is time‐consuming, requires substantial human investment, and is difficult to mobilize at large taxonomic scales. We created and evaluated new methods based on deep learning techniques to automate annotation of phenological stages and tested these methods on four herbarium data sets representing temperate, tropical, and equatorial American floras. Results: Deep learning allowed correct detection of fertile material with an accuracy of 96.3%. Accuracy was slightly decreased for finer‐scale information (84.3% for flower and 80.5% for fruit detection). Discussion: The method described has the potential to allow fine‐grained phenological annotation of herbarium specimens at large ecological scales. Deeper investigation regarding the taxonomic scalability of this approach is needed.